The hooded hawk mystery - Dixon, Franklin W. (New York, Grosset & Dunlap, 1971)
When their peregrine falcon brings down a homing pigeon carrying rubies, the Hardy brothers find themselves involved with kidnappers.
Originally published in 1954.
Keywords: Mystery and detective stories